2016
DOI: 10.1111/cup.12867
|View full text |Cite
|
Sign up to set email alerts
|

Immunostain use in the diagnosis of melanomas referred to a tertiary medical center: a 15‐year retrospective review (2001–2015)

Abstract: Immunostain use in the diagnosis of melanoma has increased significantly in the past 15 years for reasons that remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Studies have shown that 95% of surveyed dermatopathologists endorse using IHC use for at least some of the melanocytic lesions encountered in practice . Kim et al found an increase in the use of IHC stains, from 5% to 25%, in melanomas referred to a tertiary center over a 10‐year period . Other investigators have found that IHC stains contributed to the diagnosis, or added information, in 33% of review cases although exactly what was added and the value of these additions was not expounded on …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that 95% of surveyed dermatopathologists endorse using IHC use for at least some of the melanocytic lesions encountered in practice . Kim et al found an increase in the use of IHC stains, from 5% to 25%, in melanomas referred to a tertiary center over a 10‐year period . Other investigators have found that IHC stains contributed to the diagnosis, or added information, in 33% of review cases although exactly what was added and the value of these additions was not expounded on …”
Section: Discussionmentioning
confidence: 99%
“…33 To improve detection and diagnosis of melanoma (as well as other cancers), non-invasive imaging technology prebiopsy and more quantitative techniques post-biopsy, such as fluorescence in situ hybridization (FISH), comparative genomic hybridization (CGH), sequencing, mass spectrometry (MS) and IHC are being used more frequently. 34,35 Non-invasive imaging for melanoma detection Recent technological advancements have resulted in the emergence of non-invasive imaging technology to detect melanoma. Several smartphone applications, such as SkinVision, UMSkinCheck, and MoleScope, have been developed with purported goals of wide-spread accessibility, cost-effective screening, and ultimately increased early detection for patients.…”
Section: Diagnosis and Prognosis Of Melanomamentioning
confidence: 99%
“…[47][48][49][50] Moreover, as the molecular mechanisms driving melanomagenesis have become better understood, researchers and clinicians have utilized molecular biomarkers to assist in recognition of melanoma, and immunohistochemistry (IHC) has been increasingly utilized in the interpretation of difficult cases. 34 IHC is the most common ancillary technique used by pathologists to assist in the diagnosis of melanoma as it is readily available in most laboratories, relatively inexpensive, and reliable and reproducible. Therefore, it is unsurprising that the use of IHC for the diagnosis of melanoma has significantly increased over the last 20 years.…”
Section: Clinical Markersmentioning
confidence: 99%
See 2 more Smart Citations